Randomized clinical trial of the effect of a fibrin sealant patch on pancreatic fistula formation after pancreatoduodenectomy. Issue 7 (17th April 2018) - Schindl, M; Függer, R; Götzinger, P; Längle, F; Zitt, M; Stättner, S; Kornprat, P; Sahora, K; Hlauschek, D; Gnant, M
Abstract: Background: The potential for a fibrin sealant patch to reduce the risk of postoperative pancreatic fistula (POPF) remains uncertain. The aim of this study was to evaluate whether a fibrin sealant patch is able to reduce POPF in patients undergoing pancreatoduodenectomy with pancreatojejunostomy. Methods: In this multicentre trial, patients undergoing pancreatoduodenectomy were randomized to receive either a fibrin patch (patch group) or no patch (control group), and stratified by gland texture, pancreatic duct size and neoadjuvant treatment. The primary endpoint was POPF. Secondary endpoints included complications, drain-related factors and duration of hospital stay. Risk factors for POPF were identified by logistic regression analysis. Results: A total of 142 patients were enrolled. Forty-five of 71 patients (63 per cent) in the patch group and 40 of 71 (56 per cent) in the control group developed biochemical leakage or POPF ( P = 0·392). Fistulas were classified as grade B or C in 16 (23 per cent) and ten (14 per cent) patients respectively ( P = 0·277). There were no differences in postoperative complications (54 patients in patch group and 50 in control group; P = 0·839), drain amylase concentration ( P = 0·494), time until drain removal (mean(s.d.) 11·6(1·0) versus 13·3(1·3) days; P = 0·613), fistula closure (17·6(2·2) versus 16·5(2·1) days; P = 0·740) and duration of hospital stay (22·1(2·2) versus 18·2(0·9) days; P = 0·810) between the two groups. Multivariable logistic regression analysis confirmed that obesity (odds ratio (OR) 5·28, 95 per cent c.i. 1·20 to 23·18; P = 0·027), soft gland texture (OR 9·86, 3·41 to 28·54; P < 0·001) and a small duct (OR 5·50, 1·84 to 16·44; P = 0·002) were significant risk factors for POPF. A patch did not reduce the incidence of POPF in patients at higher risk. Conclusion: The use of a fibrin sealant patch did not reduce the occurrence of POPF and complications after pancreatoduodenectomy with pancreatojejunostomy. Registration number: 2013-000639-29 (EudraCT register). Abstract : Not effective in reducing complications